1977
DOI: 10.1203/00006450-197706000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Valine on Propionate Metabolism in Control and Hyperglycinemic Fibroblasts and in Rat Liver

Abstract: Fibroblastspropionyl-CoA carboxylase methylmalonic acidemia r a t liver methylmalonyl-CoA m u t a s e valine nonketotic hyperglycinemia Effect of Valine on Propionate Metabolism in Control and Hyperglycinemic Fibroblasts and in Rat Liver B E l T Y REVSIN,'36' JOYCE LEBOWITZ, AND GRANT MORROW I11Deparrrtlenr of Pediarrics, Uttiversity of Arizona College of Medicine, Arizona Medical Center, Tucson, Arizona, USA Summary propionic acidemia (3), and isovaleric acidemia (2), whereasMeasurement of methylmalonyl-CoA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Propionyl-CoA is produced by catabolism of c holesterol, v aline, o dd chain fatty acids, m ethionine, i soleucine and t hreonine (c-VOMIT) [2, 1618]. Like other carboxylases, PCC is promiscuous and can carboxylate several other acyl-CoAs, but has greatest affinity for propionyl-CoA (Km = 0.29 mM).…”
Section: Reviewmentioning
confidence: 99%
“…Propionyl-CoA is produced by catabolism of c holesterol, v aline, o dd chain fatty acids, m ethionine, i soleucine and t hreonine (c-VOMIT) [2, 1618]. Like other carboxylases, PCC is promiscuous and can carboxylate several other acyl-CoAs, but has greatest affinity for propionyl-CoA (Km = 0.29 mM).…”
Section: Reviewmentioning
confidence: 99%
“…The nonketotic syndrome was originally thought to be present only with the defect in oxidation of glycine and without altered propionic or methylmalonic acid metabolism (Baumgartner and Wick, 1972;Baumgartner et at., 1975). However, more recent reports have provided evidence for other metabolic defects associated with the nonketotic syndrome (Wada et at., 1972;Krieger and Hart, 1974;Corbeel et aI., 1975;De Groot et at., 1975;Geison et aI., 1975;Farriaux et aI., 1976;Kolvraa et aI., 1976;Revsin et at., 1977).…”
Section: Cytoplasmic Poolmentioning
confidence: 99%
“…It may be relevant that Revsin et al. (35), reported a 59% decrease in the activity of propionyl-CoA carboxylase in lysates of fibroblasts derived from a patient with nonketotic hyperglycinemia, and Stumpfet al (36) showed that propionyl-CoA is a potent inhibitor of succinylCoA ligase; half-maximal inhibition occurred at 0.2 mM propionyl-CoA. In any case the observed reduction in the activity of the P-protein does not appear to be an artifact of storage of the liver.…”
Section: Discussionmentioning
confidence: 99%